Viscosidad de suspensiones estables y de preparaciones extemporáneas de eritromicina” - Meza Valles, Sussy Ivonne (2010)
We worked with samples of Erythromycin 250mg / 5 mL x 60mL extemporaneous preparation of suspensions of which corresponded to the laboratories Farmindustria, IQ Farma (Erytrom), LCG and samples of stable suspensions of erythromycin 250mg / 5 mL x 60mL. Cipa laboratory (Ilosone) and Genf, studied its rheological behavior and viscosity was determined by using the V1 LABOLAN rotary viscometer (Brookfield type), the analysis was conducted for 8 days under constant temperature and time. From the results obtained samples of suspensions prepared extemporaneously presented different rheological behaviors, while stable suspensions showed the same rheological behavior. Thus Farmindustria laboratories (suspensions prepared extemporaneously) and Cipa Genf (stable suspensions) showed thixotropic behavior, this being the ideal for this type of dosage form. Pharma IQ's lab presented a Newtonian behavior and the LCG laboratory presented a pseudoplastic behavior, unwanted behaviors in the pharmaceutical form. In addition, calculate the average coefficient of variance and F ratio with which contrasted whether there was significant difference between days of analysis and stable extemporaneous suspensions was determined that stable suspension samples were more similar in their results compared with extemporaneous preparation samples that showed a greater difference. It was found that the biggest difference to the laboratories belonged IQ Farma and LCG have the same rheological behavior that ensures stability over time